Hydraulic parameters estimation from well logging resistivity and geoelectrical measurements - Perdomo, Santiago (2014)
In this paper, a methodology is suggested for deriving hydraulic parameters, such as hydraulic conductivity or transmissivity combining classical hydrogeological data with geophysical measurements. Estimates values of transmissivity and conductivity, with this approach, can reduce uncertainties in numerical model calibration and improve data coverage, reducing time and cost of a hydrogeological investigation at a regional scale. The conventional estimation of hydrogeological parameters needs to be done by analyzing wells data or laboratory measurements. Furthermore, to make a regional survey many wells should be considered, and the location of each one plays an important role in the interpretation stage. For this reason, the use of geoelectrical methods arises as an effective complementary technique, especially in developing countries where it is necessary to optimize resources. By combining hydraulic parameters from pumping tests and electrical resistivity from well logging profiles, it was possible to adjust three empirical laws in a semi-confined alluvial aquifer in the northeast of the province of Buenos Aires (Argentina). These relations were also tested to be used with surficial geoelectrical data. The hydraulic conductivity and transmissivity estimated in porous material were according to expected values for the region (20m/day; 457m2/day), and are very consistent with previous results from other authors (25m/day and 500m2/day). The methodology described could be used with similar data sets and applied to other areas with similar hydrogeological conditions.